2017
DOI: 10.4330/wjc.v9.i9.749
|View full text |Cite
|
Sign up to set email alerts
|

Utility and correlation of known anticoagulation parameters in the management of pediatric ventricular assist devices

Abstract: AIMTo assess utility and correlation of known anticoagulation parameters in the management of pediatric ventricular assist device (VAD).METHODSRetrospective study of pediatric patients supported with a Berlin EXCOR VAD at a single pediatric tertiary care center during a single year.RESULTSWe demonstrated associations between activated thromboplastin time (aPTT) and R-thromboelastography (R-TEG) values (rs = 0.65, P < 0.001) and between anti-Xa assay and R-TEG values (rs = 0.54, P < 0.001). The strongest correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…While some previous studies in people demonstrated a correlation between viscoelastic testing variables and anti-Xa activity, such findings were not consistent. 16,[27][28][29] One small experimental study in healthy dogs demonstrated a strong correlation between TEG variable r-time and anti-Xa activity. 30 Anti-Xa activity is not commonly used for monitoring people receiving LMWH.…”
Section: Discussionmentioning
confidence: 99%
“…While some previous studies in people demonstrated a correlation between viscoelastic testing variables and anti-Xa activity, such findings were not consistent. 16,[27][28][29] One small experimental study in healthy dogs demonstrated a strong correlation between TEG variable r-time and anti-Xa activity. 30 Anti-Xa activity is not commonly used for monitoring people receiving LMWH.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, TEG has been applied in various clinical scenarios such as liver transplant, trauma or pre-and post-ventricular assist device (VAD). [29][30][31][32] These publications have described in detail the utilization of TEG for detection of coagulopathy as well as for TEG guided therapies including our previous work on use of TEG during VAD therapy. 32 Only recently, TEG guided heparin therapy was tested in a pilot study in adult ECMO and showed less adjustment and lower dose needs for heparin without adverse impact.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] These publications have described in detail the utilization of TEG for detection of coagulopathy as well as for TEG guided therapies including our previous work on use of TEG during VAD therapy. 32 Only recently, TEG guided heparin therapy was tested in a pilot study in adult ECMO and showed less adjustment and lower dose needs for heparin without adverse impact. 33 A study looking at the predicting thrombotic complications in ECMO found that Anti-Xa levels and TEG R values were predictive of thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…Only one small retrospective study exists comparing TEG and anti-Xa levels in which a moderate correlation between TEG reaction time and anti-Xa activity was demonstrated in pediatric heart failure patients. 39…”
Section: Discussionmentioning
confidence: 99%